Analisis Kausalitas Belanja Infrastruktur Terhadap Pertumbuhan Ekonomi pada 46 Negara di Dunia - Sulfayanti Fadila Mahera; Herwin Mopangga; Boby Rantow Payu (Economic Reviews Journal, 2025)
This research analyzes the influence of infrastructure spending on economic growth in 46 countries during the 2018–2023 period. Using a quantitative approach with secondary data from the World Bank, analysis was carried out through panel data regression using Fixed Effect, Random Effect and Generalized Least Squares (GLS) models. The results show that spending on infrastructure, air transportation and electricity does not have a significant effect on economic growth. The Fixed Effect model was chosen as the best model, but the coefficient of determination value is low, indicating that these variables are not sufficient to explain variations in economic growth. These findings emphasize the importance of efficiency, governance and sector linkages in maximizing the impact of infrastructure spending on economic growth.